3^(2x) - 3^(x2) = 3^(x) -9怎么算啊
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 04:06:32
3^(2x)-3^(x2)=3^(x)-9怎么算啊3^(2x)-3^(x2)=3^(x)-9怎么算啊3^(2x)-3^(x2)=3^(x)-9怎么算啊令3^x=y9y-y^2=y-9解得y=-1(舍去
3^(2x) - 3^(x2) = 3^(x) -9怎么算啊
3^(2x) - 3^(x2) = 3^(x) -9怎么算啊
3^(2x) - 3^(x2) = 3^(x) -9怎么算啊
令 3^x=y
9y-y^2=y-9
解得y=-1(舍去)或9
3^x=9
x=2
希望对你有用
(x2-3x)2-x(x2-3x)-2x2
解方程:X2--1/8(X2+2X)+X2+2X/3(X2--1)=11
5(x2-x)=3(x2+x)
解方程:(x2-3x+2)(x2+3x-2)=x2(x+3)(x-3)
(x2-3x+2) (x2+3x-2)=x2(x+3)(x-3)解方程
3/x2 -3x+2-1/x-2=1/x2 -x+4/x2 -2x
(3x2-x)2-3(3x2-x)=2
已知x2-4x+1=0,求x2/(x2)2-3x2+1
y=(x2+2x)/(x2+2x+3) 值域x2 是x方
解方程:1/x2+x +1/x2+3x+2 +1/x2+5x+6 +1/x2+7x+12 +1/x2+9x+20=5/x2+11x-708解方程:1/x2+x +1/x2+3x+2 +1/x2+5x+6 +1/x2+7x+12 +1/x2+9x+20=5/x2+11x-708
x2-2x-3
X2-2X-3
-x2+2x-3
(x-x2)(x2+x-6)分之(x2+3x)(x2-3x+2)
1/(x2+x)+1/(x2+3x+2)+1/(x2+5x+6)+1/(x2+7x+12)=4/21x2是x的平方
x2-3x+1=0 x2/(x4-x2+1)
解分式方程:2/x2+5x+6 + 3/x2+x-6=4/x2-4
解方程2/x2+x+3/x2-x=4/x2-1